The Afghan Shia and the Second Islamic Emirate (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
After the return to power of the Taliban in August 2021, many analysts wondered if the new Islamic emirate would be different from the one that had controlled much of the country between 1996-2001. The treatment of women since then, which has received extensive coverage, seems to indicate that their ideological stand has not changed. But there is one aspect that has been overlooked and that would help us answer that question: the policies towards the Shi‘a minority. In the paper we will summarize the status of Afghan Shi‘as through the decades and assess whether it has changed over the course of two periods of Taleban rule
Keywords: Afghanistan; Shi‘as; Ismailis; Taleban